Ritual Ider Bumi Di Desa Kemiren, Kecamatan Glagah, Kabupaten Banyuwangi - Sulistyani (Institut Seni Indonesia Denpasar, 2008)
Ritual Ider Bumi one of existing ceremony ritual society of Using Banyuwangi, as statement or expression thank goodness for blessing which have been accepted to the countryside security during one year. Society Using is original society Banyuwangi, (those who do not want to coexist with the society urban). Society Using in Ke- miren village, its confidence embrace the Islam, but also still run the culture which inherit from its ancestor. Religion and cultural walk along, till able to form the ceremony ritual like that ceremony of ritual Ider Bumi executed in each feast day of Ramadan Idul Fitri.